The effectiveness of kegel exercise in reducing perineal laceration during vaginal delivery - Puspitasari, Lina; Babazadeh, Raheleh (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2025)
Background: Perineal laceration is a common complication during vaginal delivery, and its severity may influence maternal recovery and postpartum quality of life. Pelvic floor muscle exercises, including Kegel exercises and Pelvic Floor Muscle Training (PFMT), are believed to enhance perineal elasticity and reduce the risk of laceration. Objective: To assess the effectiveness of Kegel exercises and PFMT in reducing the degree of perineal laceration among postpartum mothers. Methods: A quasi-experimental study with a posttest-only nonequivalent control group design was conducted among 60 pregnant women, who were assigned to either an intervention group (antenatal exercises with PFMT) or a control group. The degree of perineal laceration was assessed after delivery. Data were analyzed using an independent t-test. Results: The findings indicated a statistically significant difference between the intervention and control groups. The mean degree of perineal laceration was lower in the intervention group (0.77 ± 0.879) than in the control group (1.73 ± 0.583), with a p-value of 0.001 and a t-value of 5.915. Conclusions: This study demonstrated that Kegel exercises and Pelvic Floor Muscle Training (PFMT) are effective in reducing the degree of perineal laceration among postpartum mothers. The intervention group showed significantly lower laceration grades compared to the control group, indicating that these pelvic floor exercises can serve as a beneficial preventive strategy. These findings confirm that Kegel exercises and PFMT meet the study objective by contributing to a measurable reduction in perineal trauma during childbirth.